Coordination compounds built up from MIICl2 and 3-cyanopyridine: double chains, single chains and isolated complexes. Issue 29 (28th June 2019) - Heine, Miriam; Fink, Lothar; Schmidt, Martin U.
Abstract : Crystal structures of [M II Cl2 (3-CNpy) x ], with M = Mn, Fe, Co, Ni, Cu, Zn and x = 1, 2, were determined by X-ray powder diffraction. Surprisingly, 3-cyanopyridine coordinates monodentately only. Abstract : The coordination polymers [M II Cl2 (3-CNpy)2 ] n, with 3-CNpy = 3-cyanopyridine and M II = Mn, Fe, Co, Ni, Cu, Zn (1a–6a ), were synthesised and the related structures determined by X-ray powder diffraction (XRPD). In1a–5a the metal atoms are octahedrally coordinated by four chlorine atoms and two 3-CNpy ligands. The Cl atoms are bridging two M atoms, leading to infinite [M II Cl2 ] n chains. The 3-CNpy molecules coordinate through their pyridine N atoms (Npy ) and form lateral "wings" on the chains. Upon heating to 230–290 °C, compounds1a–5a release half of the organic ligands and transform into [M II Cl2 (3-CNpy)1 ] n (1b–5b ). The crystal structures of1b and3b–5b were also determined from X-ray powder data. Compounds1b and3b–5b are built up by double chains of [M2 II Cl4 ] n units. Each metal atom is coordinated by two μ2 - and three μ3 -bridging chlorine atoms and one 3-CNpy ligand. In none of the investigated compounds does the 3-CNpy molecule act as a bridging ligand, which is in contrast to [M II Br2 (3-CNpy)1 ] n . The compound [Zn II Cl2 (3-CNpy)2 ] shows two polymorphic forms (α -6a andβ -6a ). In both polymorphs, the Zn atoms are tetrahedrally coordinated by two chlorine atoms and two 3-CNpy ligands to form discrete complexes. Upon heating to 290 °C, α -6a andβ -6a decompose into ZnCl2 and 3-CNpy without forming intermediate phases. In all compounds, the coordination mode of the 3-CNpy ligand was investigated by IR spectroscopy.